Image and graphics : 8th international conference, ICIG 2015, Tianjin, China, August 13-16, 2015 : proceedings /: 8th international conference, ICIG 2015, Tianjin, China, August 13-16, 2015 : proceedings. (2015) - Unknown
No abstract available